The Effect of Soaking and Boiling on Physical and Chemical Properties of Read Kidney Beans Instant - Nirmagustina, Dwi Eva; Wirawati, Chandra Utamai; Handayani, Sri; Khoerunnisa, Tiara Kurnia; Rani, Hertini (ABEC Indonesia, 2024)
Red kidney beans are a plant-based food that contains protein, carbohydrates, dietary fiber, vitamins, and minerals,. Redkidney beans take a long time to cook and have a rough texture. As a result, instant red kidney beans must be developed. Soaking,boiling, and drying are the steps in the production of instant goods. The objective of this research was to determine the physicaland chemical characteristic of soaked-boiled red kidney beans and instant red kidney beans based on soaking and boiling times.The study used a factorial completely randomized block design. The first factor was soaking time, which had three treatments (0hours, 6 hours, and 12 hours). The second factor was cooking time, which had three treatments (0 minutes, 10 minutes, or 20minutes). The study was carried out three times. Data analysis was conducted statistically using analysis of variance (ANOVA) ata 5% significance level to determine the effect of treatment on test parameters. If the treatment has a significant effect, a furtherDuncan test will be conducted to determine the differences between treatments. The results showed that soaking and boiling affectedthe physical and chemical characteristics of instant red beans. The weight, yield, and hydration capacity of instant red beansincreased with the longer soaking and boiling, and the hardness, density of the kamba, and color intensity of instant red beansdecreased with the longer soaking and boiling. Soaking for 6 hours and boiling for 10 minutes was the optimal time to produceinstant red beans. The physical and chemical characteristics of instant red beans included weight 161.5 g, density of kamba 0.71g/ml, hardness 2.83 cm/kg, hydration capacity 66.67%, water content 8.02%, and soluble protein 6.71%.